M-elite coevolutionary kinetic-molecular theory optimization algorithm - Chao-dong FAN; Jing ZHANG; Ling-zhi YI (Tongxin xuebao)
M-elite coevolutionary kinetic-molecular theory optimization algorithm (MECKMTOA) was proposed.MECKMTOA uses M elites to avoid misleading,improves the convergence precision by learning and collaboration among the elites,employs a new wave operator to prevent premature by dimension.The results show that MECKMTOA has good performance in precision and stability,and can solve the high-dimensional function optimization problems well.